COVID-19 vaccination: The impact on the selection criteria of the convalescent plasma donors - Bansal, N. (Transfus Clin Biol, 2021)
Clinical management protocols for COVID-19 are evolving rapidly as more information about the epidemiology and pathophysiological changes in COVID-19 become available. However, no definite treatment of COVID-19 has been found till date. The COVID-19 convalescent plasma (CCP) therapy has emerged as an important investigational therapy in the management of COVID-19 patients. Additionally, the regulatory agencies, in particular, the Indian blood transfusion council must release some interim recommendations for the blood centres on the CCP blood donor eligibility criteria after COVID-19 vaccination. More clinical trials are needed to know the efficacy of the CCP harvested from COVID-19 recovered individuals who have been vaccinated against those COVID-19 recovered individuals who are not vaccinated to understand the vaccine impact on the IgG titres of anti-SARS-CoV-2 antibodies.